Distinct element modelling of the material removal process in conventional and Laser Assisted Machining of silicon nitride ceramics. (27th January 2009) - Yang, Budong; Shen, Xinwei; Lei, Shuting
This paper applies distinct element method (DEM) to simulate the material removal in conventional and Laser Assisted Machining (LAM) of silicon nitride ceramics. Simulation results demonstrate that DEM can reproduce the initiation and propagation of cracks, chip formation process and material removal mechanisms. Material removal is mainly realised by propagation of lateral cracks in both conventional and LAM. Crushing-type material removal is an important mechanism in conventional machining but not in LAM. The lateral cracks in LAM are easier to propagate to form larger chips. LAM creates less and smaller median cracks, therefore has less surface/subsurface damage than conventional machining. [Received 14 February 2008; Revised 30 June 2008; Accepted 4 August 2008]